2020
DOI: 10.2337/db20-0147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Long Noncoding RNA lnc-URIDS Delays Diabetic Wound Healing by Targeting Plod1

Abstract: Impaired wound healing is one of the main causes of diabetic foot ulcerations. However, the exact mechanism of delayed wound healing in diabetes is not fully understood. Long noncoding RNAs (lncRNAs) are widely involved in a variety of biological processes and diseases, including diabetes and its associated complications. In this study, we identified a novel lncRNA, MRAK052872, named lncRNA UpRegulated in Diabetic Skin (lnc-URIDS), which regulates wound healing in diabetes. lnc-URIDS was highly expressed in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…31 These data support therapeutic application of MSC-derived exosomes carrying lncRNA H19 for improved diabetic fibroblast function. 30 A study by Hu et al 32 showed that lncRNA URIDS (Upregulated in Diabetic Skin) is highly expressed in diabetic skin and upregulated in dermal fibroblasts treated with advanced glycation end products (AGE). Silencing of lncRNA URIDS promoted migration of diabetic fibroblasts despite AGE treatment and accelerated wound closure in vivo.…”
Section: Long Non-coding Rnas In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…31 These data support therapeutic application of MSC-derived exosomes carrying lncRNA H19 for improved diabetic fibroblast function. 30 A study by Hu et al 32 showed that lncRNA URIDS (Upregulated in Diabetic Skin) is highly expressed in diabetic skin and upregulated in dermal fibroblasts treated with advanced glycation end products (AGE). Silencing of lncRNA URIDS promoted migration of diabetic fibroblasts despite AGE treatment and accelerated wound closure in vivo.…”
Section: Long Non-coding Rnas In Wound Healingmentioning
confidence: 99%
“…The lncRNA URIDS regulates wound healing through interaction with PLOD1 (Procollagen-lysine, 2-oxoglutarate 5-dioxygenase 1), which results in decreased PLOD1 protein stability and deregulation of collagen production and ultimately delayed healing. 32 Another lncRNA TETILA (TET2-interacting long non-coding RNA) was found upregulated in human diabetic skin, 33 where it activates transcription of MMP-9 (Matrix Metalloprotease 9), an indicator of poor wound healing in DFUs. 34,35 Silencing of TETILA increased migration of diabetic keratinocytes even in the presence of AGE.…”
Section: Long Non-coding Rnas In Wound Healingmentioning
confidence: 99%
“…Lnc‐RNA MRAK052872 (named lnc‐URIDS) is dramatically increased not only in the diabetic skin, but also in the serum of type 2 DM patients with DFU, indicating its participation in wound healing of diabetes 73 …”
Section: Lncrnas and Maturation Phasementioning
confidence: 99%
“…Hu et al annotated and characterized a novel lncRNA, MRAK052872, which was significantly upregulated in the fibroblasts of the dermal layer in diabetic skin tissue. 105 Therefore, this lncRNA was later named URIDS (UpRegulated in Diabetic Skin). They further studied its function by knocking down the expression of URIDS and found that the migration of AGE-treated fibroblasts was significantly increased.…”
Section: Remodeling Stagementioning
confidence: 99%